Estimate of the non-calorimetric energy of showers observed with the fluorescence and surface detectors - Tueros, Matias Jorge (2013)
The determination of the primary energy of extensive air showers using the fluorescence technique requires an estimation of the energy carried away by particles that do not deposit all of their energy in the atmosphere. This estimation is typically made using Monte Carlo simulations and thus depends on the assumed primary particle composition and model predictions for neutrino and muon production. In this contribution we introduce a new method to obtain the invisible energy directly from events measured simultaneously with thefluorescence and the surface detectors of the Pierre Auger Observatory. The robustness of the method, which is based on the correlation of the invisible energy with the muon number at ground, is demonstrated by applying it to different sets of Monte Carlo events. An event-by-event estimate of the invisible energy is given for the hybrid data set used for the energy calibration of the surface detector of the Pierre Auger Observatory.